INDICATORS OF PORK QUALITY WHILE FEEDING WITH “EFIPROT” PVMS - Vuhliar, V. S. (Scientific Progress & Innovations, 2020)
The study of using “Efiprot” protein-vitamin-mineral supplement (PVMS) was conducted on three ana-logue groups of Large White breed young pigs, 12 heads in each. Animals were grown in the same condi-tions during the whole study period, changing only the weight of each diet component and the amount of the PVMS. During the rearing period, the animals consumed food according to growth phases, its quantity in-creased from 1 kg/head (8–15 kg of live weight) up to 1.5 kg/head per day (15–35 kg of live weight) and from 2 kg/head (35–65 kg of live weight) and up to 2.5 kg/head per day (65–110 kg of live weight). It has been established that as a result of scientific studies at feeding with “Efiprot” protein-vitamin-mineral supplement with different doses of essential oils in the diet, it contributed to better feed intake and increase in the aver-age daily weight gain by 4.1 and 7.1 % as compared with the control. According to the results of the control slaughter of fattening pigs, it was found that slaughter weight of the experimental groups, which received “Efiprot” PVMS was higher as compared with the control by 4.82 and 8.37 kg depending on the supplement dose and slaughter output – by 2.6 and 4.6 % higher. Also, feeding with the PVMS contributed to better car-cass weight indices – an increase of 4.3–7.3 kg, carcass output index exceeded the control value by 4.63–5.73 %, muscle tissue output – by 0.79–0,49 % and fat tissue – by 0.2 % in the third group, with a decrease in bone – by 0.65% – 0.69 %. The studied indicators of basting back fat thickness in two experimental groups of animals in different anatomical carcass parts increased by 10.04–13.17 % in comparison with the control. There was also a tendency to increasing the thickness in the area of the neck (18.79–7.29 %), but-tocks (18.03–40 %) as compared with the control, and the indicators in the withers were higher by 9.43 % in the second group and in the hind loin – by 23,67 % in the third group. The average back fat thickness in-creased by 10.04–13.18 % in the second and third groups.